The Student SOM Survey 1993 - SOM Institute, University of Gothenburg (University of Gothenburg, 1995)
The SOM-institute at Göteborg University carries out two annual surveys. One is a nation-wide survey, while the other is carried out in Western Sweden. To be able to shed light on opinions and habits of the student generation of today a similar survey was carried out among the students at Göteborg University. The questionnaire was divided into seven parts: mass media; politics and society; energy, nuclear power and environment; Sweden and the rest of the world; leisure-time activities; background; and study programme. Questions concerning mass media dealt with news in radio and television; morning paper reading; international papers and magazines; confidence in how various institutions and groupings handle their work; and how important it is to get news from various areas/countries. Politics and society deals with interest in politics; important issues; opinion on a number of proposals occurring in the political debate; opinion on how the government handle their work; position on the political left-right scale; opinion on a Swedish EC-membership; attitude toward the political parties and the party leaders; qualities possessed by Ingvar Carlsson, Carl Bildt, and Gudrun Schyman; party most liked and second best respectively. Questions about energy, nuclear power and environment dealt with opinion on nuclear power in Sweden; treatment of nuclear power disposals; threats against the environment; opinion on a number of proposals occurring in the Swedish environmental debate; threats against life and health. Questions concerning Sweden and the rest of the world dealt with worries for the future; refugees and immigrants; how a Swedish EC-membership would affect a number of sectors, and opinion on a number of proposals concerning Sweden´s relations to the rest of the world. Leisure-time activities dealt with television channels watched; general impression of the Swedish television channels; activities during the last year; and organisation membership and activities. Background include information on place the respondent grew up on, age, gender, marital status, household equipment, economical changes, and opinion on party best suited to solve the economical problems in Sweden. Questions concerning study programme included educational background, experiences of basic courses, present course compared to other courses.

Purpose:

To find out how students feel about their education and the social environment at the University of Gothenburg

SOM-institutet vid Göteborgs universitet genomför årligen två frågeundersökningar. Den ena är nationell medan den andra baseras på ett urval i Västsverige. För att fånga upp åsikter och vanor hos dagens studentgeneration genomfördes en liknande undersökning bland studenterna på Göteborgs universitet. Urvalet utgjordes av grundstudenter vid Förvaltningshögskolan, Statsvetenskapliga institutionen och Institutionen för journalistik och masskommunikation, de institutioner som tillsammans bildat SOM-institutet. Frågeformuläret indelades i massmedia; politik och samhälle; energi, kärnkraft och miljö; Sveriges förhållande till omvärlden; fritidsintressen; bakgrund; samt kurs/linje. Frågor om massmedia behandlar vilka nyhetsprogram i radio och TV man tar del av, vilken morgontidning man läser och hur man har tillgång till den, om man läser utländsk tidning eller tidskrift, vilket förtroende man har för hur olika samhällsinstitutioner och grupper sköter sitt arbete samt hur viktigt man tycker det är att få nyheter från ett antal områden/länder. Avsnittet om politik och samhälle tar upp det politiska intresset, viktiga samhällsproblem, inställning till ett antal förslag som förekommer i den politiska debatten, inställning till hur regeringen sköter sin uppgift, placering på vänster-högerskalan, åsikt om ett svenskt medlemskap i EG, inställning till de politiska partierna och partiledarna, egenskaper hos Ingvar Carlsson, Carl Bildt och Gudrun Schyman samt vilket parti man tycker bäst resp. näst bäst om. Frågor om energi, kärnkraft och miljö tar upp åsikt om kärnkraftens användning i Sverige, hantering och slutförvaring av kärnkraftens avfall, hur allvarliga hot mot miljön olika miljöproblem är, inställning till ett antal förslag i den svenska miljödebatten, samt risker för det egna livet och hälsan. Avsnittet om Sveriges förhållande till omvärlden tar upp saker som oroar inför framtiden, omständigheter viktiga för att flyktingar skall få uppehållstillstånd, inställning till olika påståenden om flyktingar och invandrare, innebörden av ett svenskt EG-medlemskap på ett antal områden, samt inställning till ett antal förslag som berör Sveriges förhållande till omvärlden. Fritidsintressen tar upp vilka TV-kanaler man brukar titta på, allmänt intryck av de svenska TV-kanalerna, aktiviteter under det senaste året samt medlemskap och aktivitet i föreningar. Bakgrundsavsnittet innehåller uppgifter om uppväxtort, ålder, kön, civilstånd, hushållets utrustning, förändring i ekonomiska förhållanden samt inställning till vilket parti som bäst kan lösa Sveriges ekonomiska problem. Frågor om kurs/linje handlar om utbildningsbakgrund, hur man upplevt grundkurs/linje, nuvarande kurs/linje jämförd med andra kurser man läst på universitetet, förkunskaper samt vilket område man vill arbeta inom efter studierna avslutats.

Syfte:

Ta reda på hur studenterna uppfattar sin utbildning och den studiesociala miljön vid Göteborgs universitet
SOM-undersökningen till studenter 1993
Student-SOM 1993
Keywords: CORS; CORS; Higher and further education; Gymnasial och högre utbildning; Media; Media; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap